Ecological policies in Italy (International relations and international law Journal, 2016)
Author, evaluating the environmental situation of Italy took into account 25 parameters. These include: fumes, congestion, quality of construction. According to the survey the most ecological area is the north-east of the country. The lack of proper organization of protection of nature leads to the further destruction of forests, unsustainable use of land for construction, reducing the area of national parks, the destruction of forest fauna. As a result of depopulation of mountain villages in the abandoned lands located mostly on steep slopes increases soil erosion and the risk of landslides and floods. But in recent years, the situation began to gradually change for the better. Italy – the only country in the Group of Eight, which refused to build nuclear power plants. The government, concerned about the environmental situation in the country has taken decisive action to improve it.
Keywords: Italy; ecology; government; Big Eight; north-east of the country